Effectiveness of educational accommodations and interventions for students with ADHD: An integrative literature review (Research, Society and Development, 2026)
Objective: To critically synthesize the scientific evidence on non-pharmacological educational interventions and accommodations aimed at improving academic performance and school engagement in children and adolescents with Attention-Deficit/Hyperactivity Disorder (ADHD). Methods: This study is an integrative literature review guided by the PICO strategy. Electronic searches were conducted in PubMed, SciELO and EBSCOHost databases, including studies published in Portuguese and English between 2011 and 2025. Eligible studies addressed school-based non-pharmacological interventions, including assessment accommodations, physical classroom adaptations, organizational and self-management strategies, behavioral interventions, and technology-based approaches. The study selection process was guided by the PRISMA guidelines. Results: The findings indicate that widely implemented accommodations, such as extended testing time, provide limited and non-specific benefits for students with ADHD. In contrast, individualized interventions—particularly those targeting organizational skills, self-regulation, continuous behavioral support, and environmental modifications—demonstrated more consistent improvements in academic engagement, executive functioning, and classroom behavior. Technology-based interventions showed domain-specific cognitive benefits, especially in attention and working memory, but did not replace broader treatment approaches. Conclusion: The evidence supports the implementation of individualized, evidence-based educational interventions as a core component of multimodal ADHD management. Structured and personalized strategies appear more effective than generic accommodations, underscoring the importance of integrated school and family involvement to optimize academic outcomes.